2003
DOI: 10.1016/s0042-6989(03)00479-6
|View full text |Cite
|
Sign up to set email alerts
|

Is word recognition different in central and peripheral vision?

Abstract: Peripheral vision plays an important role in normal reading, but its role becomes larger for visually impaired people with central-field loss. This experiment studied whether lexical processing differs in central and peripheral vision through the analysis of word-frequency effects in lexical decisions. We asked two main questions: (1) Do central and peripheral vision differ in the time course of lexical processing? and (2) do central and peripheral vision differ in the quality of lexical processing? To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 29 publications
3
50
1
2
Order By: Relevance
“…This interaction is consistent with the results obtained by Lee, Legge, and Ortiz (2003), who demonstrated that the time course of frequency effects differed in central and peripheral vision, with frequency effects emerging more slowly in peripheral vision. Significant frequency effects occurred for the shortest exposures in central vision (25-50 msec), whereas significant frequency effects did not occur in peripheral vision until the exposures lasted 100 msec.…”
Section: Spatial Attention Word Frequency and Lexicalitysupporting
confidence: 92%
“…This interaction is consistent with the results obtained by Lee, Legge, and Ortiz (2003), who demonstrated that the time course of frequency effects differed in central and peripheral vision, with frequency effects emerging more slowly in peripheral vision. Significant frequency effects occurred for the shortest exposures in central vision (25-50 msec), whereas significant frequency effects did not occur in peripheral vision until the exposures lasted 100 msec.…”
Section: Spatial Attention Word Frequency and Lexicalitysupporting
confidence: 92%
“…Importantly, subjects were better at naming words than pronounceable nonwords, suggesting that they not only had processed information about the letters, but also had accessed the words' lexical entries. Lee, Legge, and Ortiz (2003) presented evidence suggesting that lexical information about a word is of the 1 Letter spaces are typically used as the metric for how far the eyes move, because the number of letters traversed by saccades is relatively invariant when the same text is read at different viewing distances, even though the letter spaces subtend different visual angles O'Regan, 1983). Fig.…”
Section: Eye Movements During Readingmentioning
confidence: 99%
“…Moving patterns that are easily separated with foveal viewing are aggregated into a single pattern in the periphery (De Bruyn, 1997). Similarly, performance declines with increased eccentricity for higher-order functions, including word recognition (Lee, Legge, & Ortiz, 2003), biological motion identification (Ikeda, Blake, & Watanabe, 2005), facial recognition (Mäkelä et al, 2001), and object detection in natural scenes (Thorpe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Adjusting scale in accordance with cortical magnification factors improves performance for measures of acuity (Virsu, Näsänen, & Osmoviita, 1987), motion coherence (van de Grind, van Doorn, & Koenderink, 1983), and letter recognition (Higgins, Arditi, & Knoblauch, 1996). However, increased stimulus scale does not equate foveal and eccentric viewing for stereopsis (Prince & Rogers, 1998), word recognition (Lee, Legge, & Ortiz, 2003), contour integration (Hess & Dakin, 1997), biological motion (Ikeda, Blake, & Watanabe, 2005), or facial recognition (Mäkelä et al, 2001). In this regard, processing such stimuli require foveal viewing for optimal performance, regardless of scale adjustments.…”
Section: Introductionmentioning
confidence: 99%